Genome-wide association study identifies seven novel susceptibility loci for primary open-angle glaucoma. (14th February 2018) - Shiga, Yukihiro; Akiyama, Masato; Nishiguchi, Koji M; Sato, Kota; Shimozawa, Nobuhiro; Takahashi, Atsushi; Momozawa, Yukihide; Hirata, Makoto; Matsuda, Koichi; Yamaji, Taiki; Iwasaki, Motoki; Tsugane, Shoichiro; et al.
Abstract: Primary open-angle glaucoma (POAG) is the leading cause of irreversible blindness worldwide for which 15 disease-associated loci had been discovered. Among them, only 5 loci have been associated with POAG in Asians. We carried out a genome-wide association study and a replication study that included a total of 7378 POAG cases and 36 385 controls from a Japanese population. After combining the genome-wide association study and the two replication sets, we identified 11 POAG-associated loci, including 4 known ( CDKN2B-AS1, ABCA1, SIX6 and AFAP1 ) and 7 novel loci ( FNDC3B, ANKRD55-MAP3K1, LMX1B, LHPP, HMGA2, MEIS2 and LOXL1 ) at a genome-wide significance level ( P < 5.0×10 −8 ), bringing the total number of POAG-susceptibility loci to 22. The 7 novel variants were subsequently evaluated in a multiethnic population comprising non-Japanese East Asians (1008 cases, 591 controls), Europeans (5008 cases, 35 472 controls) and Africans (2341 cases, 2037 controls). The candidate genes located within the new loci were related to ocular development ( LMX1B, HMGA2 and MAP3K1 ) and glaucoma-related phenotypes ( FNDC3B, LMX1B and LOXL1 ). Pathway analysis suggested epidermal growth factor receptor signaling might be involved in POAG pathogenesis. Genetic correlation analysis revealed the relationships between POAG and systemic diseases, including type 2 diabetes and cardiovascular diseases. These results improve our understanding of the genetic factors that affect the risk of developing POAG and provide new insight into the genetic architecture of POAG in Asians.